2012
DOI: 10.1016/j.jaut.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Animal models used to examine the role of the environment in the development of autoimmune disease: Findings from an NIEHS Expert Panel Workshop

Abstract: Autoimmunity is thought to result from a combination of genetics, environmental triggers, and stochastic events. Environmental factors, such as chemicals, drugs or infectious agents, have been implicated in the expression of autoimmune disease, yet human studies are extremely limited in their ability to test isolated exposures to demonstrate causation or to assess pathogenic mechanisms. In this review we examine the research literature on the ability of chemical, physical and biological agents to induce and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 117 publications
(114 reference statements)
0
51
0
Order By: Relevance
“…2,3 Silicosis is a brotic lung disease caused by the inhalation of silica dust. Occupational exposure to respirable silica particles occurs in many situations, which are oen called the dusty trades and include abrasive blasting with sand, jack hammering, drilling, mining/tunneling operations, and cutting and sawing.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Silicosis is a brotic lung disease caused by the inhalation of silica dust. Occupational exposure to respirable silica particles occurs in many situations, which are oen called the dusty trades and include abrasive blasting with sand, jack hammering, drilling, mining/tunneling operations, and cutting and sawing.…”
Section: Introductionmentioning
confidence: 99%
“…To strengthen this hypothesis we have shown that IgG4 anti-Dsg1 autoAbs cross-react with LJM11 sand fly salivary gland antigen (13), which suggests that the development of IgG4 Abs may be linked to immune responses to environmental antigens. Compared to investigations on the pathogenesis and genetic predisposition of autoimmune diseases, etiological studies regarding environmental triggers of these diseases are lacking due to low prevalence and the clinical heterogeneity of the diseases (1419). Similarly, the random nature of autoimmune skin diseases in North America makes it difficult to assess their etiological commonality and further dissect their causes.…”
Section: Introductionmentioning
confidence: 99%
“…It is extremely difficult to identify the specific causes of autoimmunity in individual patients, as it usually has contributions from a number of internal and external factors, including a genetic predisposition, age, previous immune challenges, exposure to pathogens etc., [6][7][8][9]. Even though genetic predisposition is known to play a very significant role, it is believed that some additional environmental triggers are required for the onset of autoimmunity, and these are usually represented by infections [10,11]. A very recent work has experimentally identified a gut bacterium that, when present in mice and humans, can migrate to other parts of the body, facilitating subsequent triggering of autoimmune disease in those organs [12].…”
Section: Introductionmentioning
confidence: 99%